Visit to the Disability Integrating Health Post and Its Effect on the Quality of Life of Children with Cerebral Palsy: A Multivariate Evidence from Sukoharjo, Central Java - Rohaniyati, Retno Dwi; Salimo, Harsono; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2020)
Background:  An assessment of the quality of life of children with cerebral palsy is important to be carried out, as part of the indicators of achieving health service delivery goals. To facilitate access to health services for children with disabilities, the government of Sukoharjo District established an integrated health post (posyandu) for children with disabilities called inclusion centers.  This study aimed to determine the quality of life of children with cerebral palsy who receive services at the inclusion center.Subjects and Method: his was a cross sectional study conducted in 12 inclusion centers in Sukoharjo, Central Java. A sample of 100 children with cerebral palsy (CP) aged 4-18 years old was selected by fixed disease sampling. The dependent variable was the quality of life of CP children. The independent variables were the level of gross motor function capability, parental coping, quality service, and frequency of posyandu visits. Gross motor function capability was measured by Gross Motor Funtion Classification System (GMFCS). Quality of life was measured by the Cerebral Palsy Quality of Life (CP-QOL) version of the parent proxy. Data collection used questionnaire and analyzed by a multiple linear regression run on Stata 13.Results: Better quality of life of children with cerebral palsy was influenced by lower GMFCS levels (b= -128.72; 95% CI= -220.34 to -37.10; p= 0.006), good parental coping (b= 18.87; 95% CI= 10.85 to 26.89; p<0.001), good service quality (b= 20.79; 95% CI= 9.99 to 31.59;  p<0.001), and more frequent visits to posyandu (b= 214.86; 95% CI= 56.66 to 373.15; p= 0.008).Conclusion: Quality of life of children with cerebral palsy is influenced by lower GMFCS levels, good parental coping, good service quality, and more frequent visits to posyandu.Keywords: quality of life, disability, cerebral palsy, integrating health post (posyandu)Correspondence: Retno Dwi Rohaniyati, Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta, Central Java, Indonesia. Email: retnodr16@gmail.com. Mobile: 08154626 8418.Journal of Maternal and Child Health (2020), 5(2): 193-199https://doi.org/10.26911/thejmch.2020.05.02.09